Can diaphragmatic breathing modify chest wall volumes during inspiratory loaded breathing in patients with heart failure? - Lage, Susan Martins (Braz J Phys Ther, 2018)
BACKGROUND: Some inspiratory muscle training protocols for patients with heart failure report the request of diaphragmatic breathing during inspiratory loaded breathing. However, it is unclear whether this condition modifies the chest wall volumes. OBJECTIVE: The primary purpose was to evaluate chest wall volumes during inspiratory loaded breathing as well as during inspiratory loaded breathing associated with diaphragmatic breathing in patients with heart failure. METHODS: Sixteen men with heart failure functional class I to III, aged 50(SD = 7) years were evaluated. Volumes of the pulmonary rib cage, abdominal rib cage and abdomen, as well as other breathing pattern variables, were assessed by optoelectronic plethysmography during quiet breathing, inspiratory loaded breathing, and inspiratory loaded breathing associated with diaphragmatic breathing. RESULTS: Chest wall tidal volume significantly increased from quiet breathing 0.53(SD = 0.14)L to inspiratory loaded breathing 1.33(SD = 0.48)L and to inspiratory loaded breathing associated with diaphragmatic breathing 1.36(SD = 0.48)L. A significant volume variation was observed on the three compartments (p < 0.05 for all). During inspiratory loaded breathing associated with diaphragmatic breathing, patients showed increased abdominal volume compared to quiet breathing [0.28(SD = 0.05) to 0.83(SD = 0.47)L, p < 0.001]; as well as from inspiratory loaded breathing [0.63(SD = 0.23) to 0.83(SD = 0.47)L, p = 0.044]. No significant changes were observed between the two inspiratory loaded breathing conditions on the percentages of the contribution of each chest wall compartment for the tidal volume, respiratory rate, minute ventilation, and duty cycle. CONCLUSION: When inspiratory loaded breathing was associated with diaphragmatic breathing, a higher volume in the abdominal compartment was obtained without significant changes in other breathing pattern variables.